Polanyi vs Hayek? - Mirowski, Philip (Globalizations, 2018)
Karl Polanyi and Friedrich Hayek are often portrayed as implacable intellectual opponents but their respective historical trajectories suggest some telling similarities. Here we describe some key similarities in their approach to markets, as a prelude to evaluating the political consequences of relying upon their Austrian conceptions of nature-based and constructivist framing of markets. Perhaps it is time to transcend their dichotomy.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; POLANYI, Karl, 1886-1964; POLANYI, Michael, 1891-1976; constructivism; markets; science and technology; spontaneous order

Reconfiguring the social and solidarity economy in a Danish/Nordic welfare context - Hulgård, Lars; Andersen, Linda Lundgaard (3rd EMES-Polanyi International Seminar. Welfare societies in transition. Polanyi revisited through the lens of welfare state, social democracy and solidarity economy, 2018)
When looking at definitions and understandings of the social and solidarity economy, one issue stands out as particularly significant. The issue of how it links to organizational (micro and meso level dimensions) and societal specificities. Whereas social enterprise also in the EMES ideal typical version (Borzaga & Defourny, 2001) is only indirectly linked to a Polanyian framework (Gardin, 2006), the notion of solidarity economy can hardly be understood at an elaborate level without reference to the Polanyian framework of plurality. Accordingly, in this paper we will first highlight the difference between adopting a social economy and a solidarity economy approach to social enterprise and social entrepreneurship. Within the framework of a social economy perspective, social enterprise is first defined through a set of organizational criteria leaving the relation to the broader and deeper issues of economy and democracy open. As a contrast to this, solidar-ity economy links the organizational dimension of a particular social enterprise to the broader political and economic framework of the particular society (Laville, 2010: 230 ff.). Secondly, we will present and discuss two specific social enterprises that both re-flects the diversity of social enterprise and social entrepreneurial initiatives in a Danish welfare context and provide important insights for developing theories on solidarity economy. The two initiatives differ in shape, space/geography and organizational struc-ture but are important examples of pluralism in a Danish welfare context (Andersen, 2015). Roskilde Festival and Skovgård Hotel share a number of features that place them as interesting agents of solidarity economy. They both display a differentiated activity portfolio of business; public and civil character and they display a differentiated profile of reciprocity, redistribution and democracy that place them as influential in local, regional and national/international contexts. Finally, in the concluding section we discuss how an analysis based upon solidari-ty economy differ from one based solely upon a social economy perspective, and second-ly some future perspectives for the continued evolution of the Danish/Scandinavian wel-fare model.
Keywords: Denmark; plurality; social economy; social enterprise; social entrepreneurship; solidarity economy

Re-dynamising Local Economies in the Age of Trumpism - Bauwens, Michel; Niaros, Vasilis (Journal of Futures Studies, 2017)
The article presents the authors' arguments on the political and policy response behind the rise of Trumpism according from the analysis of authors Kojin Karatani, Karl Polanyi and Mark Blyth. Topics discussed include Karatani's book "The Structure of World History" on the integration of modalities for political and economic system, Polanyi's analysis in the book "The Great Transformation" on the systemic balance and the transition in regimes of value for re-alignment of modalities.
Keywords: BLYTH, Mark; Futures studies; Great Transformation, The (Book); KARATANI, Kojin; Structure of World History: From Modes of Production to Modes of Exchange, The (Book); TRUMP, Donald; Trumpism; disembeddedness; local economies; technology

Economics Humanized - Pearson, Dan (Issues in Science & Technology, 2015)
Keywords: BLOCK, Fred L.; Power of Market Fundamentalism: Karl Polanyi's Critique, The (Book); SOMERS, Margaret R.; book review; economics; nonfiction; science and technology

Nano-worlds as Schumpeterian emergence and Polanyian double-movements - Randles, Sally; Dewick, Paul; Loveridge, Denis; Schmidt, Jan C. (Technology Analysis & Strategic Management, 2008)
The overarching question raised in this special issue is whether societies can, do or indeed should steer new and emergent science and technological development and its management on to trajectories construed as more or less 'desirable'. It therefore sits at the interface of two arenas. These are governance: processes of shaping/steering emergent technologies and markets; and sustainability: normative agendas incorporating a range of potentially competing conjectures and internally inconsistent desires such as to facilitate rather than stifle innovation, to enable economic development, to anticipate or deploy strategies to cope with risk and uncertainty, and to encourage technological developments that benefit rather than harm humans, their quality of life and the natural environment. Despite the potential for apparent empirical inconsistencies and contradictions that manifest as outcomes of the negotiation of these aims, there is (pace Karl Polanyi) a normative entry point to all of the articles and the material they draw upon, which is the idea that markets and technologies should be the handmaiden of societies, not vice versa. It is now widely recognized that 'nanotechnology' is a diverse set of feasible procedures emerging from scientific possibilities to enable the production of artefacts at the nanoscale creating new products, processes and services. Attention has to be paid to the desirability of these artefacts, which involve social, economic, ecologic, political and ethical matters that surround their emergence. The purpose of this special issue is to set out the current and future prospects for the widespread use (or innovation) of technological convergence at the nanoscale to create nano-artefacts, and the needs for governance and regulation that will accompany these innovations.
Keywords: POLANYI, Karl, 1886-1964; SCHUMPETER, Joseph Alois, 1883-1950; double movement; economic development; editorials; emergence; governance; nano-; nanotechnology; new product development; quality of life; sustainability; technological innovations

Transformation or Structural Change? What Polanyi Can Teach Us about the Platform Economy - Kenney, Martin; Zysman, John; Bearson, Dafna (2020)
The rise of the platform economy marks the latest phase in the ongoing digital revolution. Indeed, the platform is to this digital era what the factory was to the industrial era, both a symbol and an organizing mechanism. Gernot Grabher and Jonas König (2020) used Karl Polanyi’s analysis of what he termed the “great transformation” to frame the rise of platform economy. The platform economy is remarkable as it confirms Polanyi’s (and Marx’s before him) insight that the reach of the market is based upon increased commodification as it has been able to reach into ever more parts of social life. We introduced the term “platform economy” in 2015 because we recognized that the digital platforms were changing the dynamics of capitalist accumulation —- an analysis framed by regulationist school of political economy. The intuition was that the socio-technical innovation of digital online platforms was the critical fulcrum for an economic restructuring that would rewire the flows of data and ultimately money and power. The firms we have termed the “mega-platforms”, Apple, Amazon, Facebook, Google, and Microsoft, have become the most valuable and powerful firms in the world. Importantly, the reach of these platforms is global and yet local and personal. Moreover, this platform power has only been reinforced during the COVID-19 pandemic.
Keywords: COVID-19; Great Transformation; Polanyi; platform economy